HUBUNGAN KECERDASAN EMOSIONAL, PERILAKU BELAJAR DAN DUKUNGAN ORANG TUA DENGAN TINGKAT PEMAHAMAN AKUNTANSI - Megasari, Yulia; Brataningrum, Natalina Premastuti (Jurnal Pendidikan Ekonomi dan Akuntansi, 2021)
This study aimed to determine (1) the positive correlation between emotional intelligence and the level of accounting understanding, (2) the positive correlation between learning behaviors and the level of accounting understanding, and (3) the positive correlation between parent’s supports and the level of accounting understanding Sanata Dharma University. This research is descriptive correlation research which was conducted in February – March 2020. The Population of the research were 56 students of accounting study program batch 2016, Sanata Dharma University Yogyakarta. The data were collected by using questionnaire and documentation. Research data are describe using PAP type II. The hypothesis was tested by Spearman Rank Correlation. The result of study were : (1) there was no positive correlation between emotional inteliigence and the level of accounting understanding (Spearman Rank = -0,143 the value of sig, (1-tailed) = 0,156); (2) there was no positive correlation between learning behaviour and the level of accounting understanding (Spearman Rank = -0,156 the value sig. (1-tailed) = 0,129); (3) there was no positive correlation between parent’s support and the level of accounting understanding (Spearman Rank = -0,036 the value sig. (1-tailed) = 0,398)Keywords : emotional intelligence, learning behaviors, parent’s supports, and the level of accounting understanding